Evaluation of Uranium Concentration and Calculated Doses of Radiation Resulting From the Tap and Bottled Drinking Water in Babylon - middle Iraq - Hasson, Muhsen K.; Al–Kubaisi, Qusai Yaseen; Ali, Kamal Kareem (Iraqi Journal of Science, 2023)
In this study, uranium concentrations were evaluated and the annual effective dose was calculated from the consumption of bottled water and tap water used for drinking in Babylon, middle Iraq. Uranium isotopes (238U, 234U, 235U) were determined for all samples collected using the phosphorylation analyzer technique represented device (KPA). Forty-four samples were collected to cover almost all districts and regions of Babylon.  Thirty tap water samples were collected from residential neighborhoods, with 14 samples from local brand bottled water. The results show that the uranium concentrations in the tap water samples ranged from 1.66 μg.L-1 to 2.64 μg.L-1, with an average of 2.12 μg.L-1, and the bottled water samples varied from 1.06 μg.L-1 to 1.82 μg.L-1, with an average 1.47 μg.L-1. This means that the uranium contents in tap and bottled water samples are less than 15 μg.L-1 and 30 μg.L-1, which are safe values of the WHO, and the EPA respectively. The annual effective dose values of 238U, 234U, and 235U for adult consumption of tap water range between 0.67, 0.0.33, 0.74 μSv.y-1 to 1.07, 0.052, 1.18 μSv.y-1 with averages of 0.86, 0.042, 0.95 μSv.y-1, respectively. Their values in bottled water ranged from 0.43, 0.020, 0.47 μSv.y-1 to 0.73, 0.035, 0.81 μSv.y-1, with an average of 0.59, 0.029, 0.65 μSv.y-1, respectively. The value of the annual effective dose of total uranium isotopes in tap water samples ranged between 1.45 μSv.y-1 to 2.30 μSv.y-1 with an average of 0.85 μSv.y-1, whereas in bottled water varied from 0.92 to 1.58 μSv.y-1 with an average of 1.28 μSv.y-1.